Komunikacja interkulturowa w biznesie międzynarodowym - Dudziak, Anna (Przegląd Politologiczny, 2018)
Intercultural communication involves verbal and nonverbal messages. The communication process is conducted not only by means of verbal messages but also by other elements that constitute body language. This process becomes significantly more complicated when cultural contexts are also taken into account. A message which is unambiguously understood and interpreted by the representatives of one culture may have quite a different interpretation in other cultures. It is therefore highly important to take cultural context into consideration during business talks. Being ignorant of this aspect can significantly impact the results of negotiations. Are we doomed to failure caused by cultural differentiation, then? Is the cultural aspect of communication an insurmountable barrier? Certainly not. It is obvious in talks with foreigners that one cannot avoid mistakes and misunderstandings resulting from the inaccurate interpretation of words and gestures. During a time of globalization, mergers and takeovers, intercultural communication is unavoidable. Every new intercultural dialogue brings new experiences and reduces the risk of faux pas based on cultural differences.